2022
DOI: 10.3389/fpubh.2022.962852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PPARG and PPARGC1A gene polymorphisms on obesity markers

Abstract: Pediatric obesity presents a multifactorial etiology, which involves genetic traits as well, including single nucleotide polymorphisms. The aim of the study is to investigate the contribution of PPARG gene polymorphisms (namely Pro12Ala rs1801282, His447His rs3856806, and Pro115Gln rs1800571) and PPARGC1A rs8192678 SNP on the anthropometric and metabolic parameters in a population of Romanian children. We conducted a cross-sectional study of 295 Caucasian children, divided according to the body mass index (BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The prevalence of PPAR-γ2 rs1801282 (Pro12Ala) polymorphism varies across populations. According to genotype frequency, several studies have reported 0% homozygous GG in Asian Indians [31], original South African [32], while in Romanian children and Caucasian adults from Poland the frequency has ranged between 2.7 and 3.7% [33,34]. In teenagers from our region's main ethnic groups, it ranges from 3 to 5%, [27].…”
Section: Discussionmentioning
confidence: 69%
“…The prevalence of PPAR-γ2 rs1801282 (Pro12Ala) polymorphism varies across populations. According to genotype frequency, several studies have reported 0% homozygous GG in Asian Indians [31], original South African [32], while in Romanian children and Caucasian adults from Poland the frequency has ranged between 2.7 and 3.7% [33,34]. In teenagers from our region's main ethnic groups, it ranges from 3 to 5%, [27].…”
Section: Discussionmentioning
confidence: 69%
“…A missense mutation of PPARγ (rs1801282; C>G; Pro12Ala) plays an essential role in the pathogenesis of obesity. However, the impact of this polymorphism on obesity-related parameters is not clarified [136][137][138][139][140], which may result from the influence of diet and the genetic heterogeneity of various populations [141,142]. Postmenopausal overweight and obese women with Pro12Pro polymorphism of the PPARγ gene and higher lean body mass (>58% of body mass) have a bigger chance of recommended glucose levels compared to subjects with lower lean body mass [120].…”
Section: Genetic Susceptibility To Sarcopenic Obesitymentioning
confidence: 99%
“…A recent meta-analysis discovered worse metabolic parameters in obesity for the G allele carriers-including higher BMI, waist circumference, and total cholesterol [140]. Other common polymorphisms of the PPARγ gene are rs3856806; C>T; His447His, which is involved in an increased risk of obesity, coronary heart disease, or colorectal cancer, and rs1800571; Pro115Gln [137,143,144]. As SO is more common in older adults, there is a need to investigate the obesity and sarcopenia risk factors in this group.…”
Section: Genetic Susceptibility To Sarcopenic Obesitymentioning
confidence: 99%
“…In addition, the surrounding environment, including social and cultural factors, home and work environments, economic factors, and social support, can affect an individual's sensitivity and preference for particular tastes, thereby influencing their dietary choices. In genetics, polymorphisms of some specific genes, such as fat mass and obesity-associated (FTO), melanocortin 4 receptor (MC4R), leptin receptor (LEPR), peroxisome proliferator-activated receptor-gamma (PPARG), and Adiponectin, have shown effects on weight gain, suppression of appetite, and oncogenesis [20][21][22][23][24][25]. The FTO gene displayed the most robust genetic correlation with polygenic obesity.…”
Section: Introductionmentioning
confidence: 99%